Quality of life among patients with hematological cancer in a Malaysian hospital. - Das, Priscilla; Awang, Hamidin; Md. Zain, Azhar; Naing @ Noorjan, Khin Ohnmar; Md Said, Salmiah; Khalid, Bahariah (Malaysian Medical Association, 2011)
The aim of this study was to determine the prevalence of symptoms and problems in hospitalized hematological cancer patients. A cross-sectional design was carried out with 105 respondents in Ampang hospital in Kuala Lumpur. The European Organization for Research and Treatment of Cancer Quality Of Life questionnaire (EORTC QLQ-C30) was used. Patients with a minimum response of "a little" were defined as having a symptom/problem while patients with a response of "quite a bit" were classified as having a "severe symptom/problem:". The four most prevalent symptoms/ problems identified were fatigue, financial difficulties, reduced role function and reduced social function. Multiple myeloma patients (MM) were identified as having the most symptoms/problems.